2021
DOI: 10.1017/jfm.2021.217
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity and stability of hypersonic leading-edge sweep flows around a blunt body

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…2 . The bi-global solver was developed by the authors' group [22,23], where the eigenvalue spectrum is calculated using the shift-invert algorithm [24]. The parallel computation package SLEPc (http://slepc.upv.es) is called for solving the discrete generalized eigenvalue equation (26).…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
“…2 . The bi-global solver was developed by the authors' group [22,23], where the eigenvalue spectrum is calculated using the shift-invert algorithm [24]. The parallel computation package SLEPc (http://slepc.upv.es) is called for solving the discrete generalized eigenvalue equation (26).…”
Section: Numerical Methods and Validationmentioning
confidence: 99%
“…Receptivity describes the mechanism by which external disturbances (like acoustic waves, ambient turbulence, entropy fluctuations, and surface irregularities) trigger unstable modes in the boundary layer [40][41][42]. The main theoretical tools for receptivity include asymptotic analysis and multiple-mode methods [43]; Xi et al [44] recently showed that the adjoint-based bio-orthogonal eigenfunction system can be extended to complex hypersonic flows to study the global receptivity. Acoustic waves are among the most common freestream perturbations, and their receptivity in highspeed boundary layers was systematically studied by Ma and Zhong [45,46].…”
Section: Mechanisms Of Hypersonic Boundary Layer Transitionmentioning
confidence: 99%
“…There are a number of more sophisticated global-mode methods, such as the one-way Navier-Stokes (OWNS) equations [255] and the adjoint receptivity framework [44,256], which at present mainly focus on compressible laminar flows. Their extensions to turbulent flows are anticipated in the near future, to uncover more dynamic insights into wallbounded turbulence.…”
Section: Global Mode Analysismentioning
confidence: 99%
“…2019; Xi et al. 2021). The geometry is described as where is the radius of curvature at the leading edge.…”
Section: Problem Description and Governing Equationsmentioning
confidence: 99%
“…The three-dimensional boundary layer over a swept wing of infinite span is considered herein. The swept wing is modelled by a swept parabolic body, which was widely adopted in previous investigations concerning cross-flow instability (see Mack & Schmid 2010;Xu et al 2019;Xi et al 2021). The geometry is described as (2.1a,b) where r 0 is the radius of curvature at the leading edge.…”
Section: Problem Description and Governing Equationsmentioning
confidence: 99%